Translation-Transdiscipline? (translation. a transdisciplinary journal, 2021)
The note, ' Translation: a new paradigm; circulated by the editorial board of this journal as an introduction to the inaugural issue has been profoundly thought-provoking. Along with the bird's-eye view of the terrain, it agonizes about an 'epistemological crisis' confrontingthe discipline of translation studies, laments the impasse within, and looks towards 'starclingly new' ways of defining translation. lecandidly confesses to articulating the anxiety of scholars and practitioners of the discipline in 'single nation states and linguisticlimits'.